966 ADVANCED ECHOCARDIOGRAPHIC AND CMR FEATURES OF PATIENTS WITH REPAIRED TETRALOGY OF FALLOT IN THE LONG-TERM FOLLOW-UP. (15th December 2022) - Gozzi, Anna; Cuppini, Elena; Cattapan, Irene; Basso, Alessia; Fumanelli, Jennifer; Candia, Angela Di; Avesani, Martina; Sirico, Domenico; Castaldi, Biagio; Reffo, Elena; Cerutti, Alessia; Biffanti, Roberta; et al.
Abstract: Advanced echocardiographic and CMR features of patients with repaired Tetralogy of Fallot in the long-term follow-up. Anna Gozzi 1, Jolanda Sabatino 1, Elena Cuppini 1, Irene Cattapan 1, Alessia Basso 1, Jennifer Fumanelli 1, Angela Di Candia 1, Martina Avesani 1, Domenico Sirico 1, Biagio Castaldi 1, Elena Reffo 1, Alessia Cerutti 1, Roberta Biffanti 1, Giovanni Di Salvo 1 1 Department for Women's and Children's Health, University Hospital of Padova, Pediatric and Congenital Cardiology Unit, Via Nicolo` Giustiniani, 2, 35128 Padova, Italy Background: Tetralogy of Fallot (ToF) is the most common cyanotic congenital heart disease and the population of ToF repair survivors is growing rapidly. Children and, more frequently young adults, with repaired ToF develop late complications. Sudden cardiac death and life-threatening ventricular arrhythmia remain a concern in patients with repaired tetralogy of Fallot. The aim of this study was to describe and analyse advanced echocardiographic and CMR features of patients with repaired ToF in the long-term follow-up and to find non-invasive predictors of adverse prognosis. Methods: This is a retrospective cohort study. Consecutive 200 patients with repaired ToF who did not undergo pulmonary valve replacement were included. Mean age of all patients was 19 ± 8. The electrocardiographic (ECG), cardiopulmonary exercise testing (CPET), echocardiographic and cardiac magnetic resonance (CMR) data were reviewed retrospectively. Right myocardial work index (RWI) was calculated as the area of the right ventricular pressure strain loops. From RWI, Right Constructive Work (RCW), Wasted Work (RWW) and Work Efficiency (RWE) were estimated. Patients were screened according the age at surgery (<12 months and >12 months) and the time since the repair (< 25 years and ≥ 25 years). A composite end-point of major adverse cardiovascular events (sudden cardiac death, sustained and non-sustained ventricular tachycardia, resuscitated sudden cardiac death, or syncope) was used. Results: CPET values were not significantly different in patients with more than 25 years since the corrective surgery. Left ventricular ejection fraction measured either by CMR or echocardiography were slightly but significantly reduced in patients with more than 25 years since the corrective surgery. Patients with older age at surgery (>12 months) have significantly reduced V0 2 max at CPET, larger RA and LA areas and larger RV basal diameter. During a median follow-up of 2.9 years, 1 patient died suddenly, 5 had documented ventricular tachycardia, and other 4 had syncope. On univariate analysis, echocardiographic left atrial area/BSA (P=0.044) and right ventricular longitudinal strain (P=0.010) were significantly related to the combined end point. Patients with reported VT at Holter ECG presented significantly reduced right ventricular function in terms of CMR-EF, echocardiographic FAC and RWI. Finally, TOF patients with borderline/impaired predicted VO2 max at CPET presented with significantly reduced RV freewall longitudinal strain and right ventricular myocardial work index. Conclusion: Long-term survival and clinical condition after surgical correction of ToF in infancy is generally good and the late functional status in ToF - operated patients could be excellent up to 25 years after the repair. However, patients with older age at surgery have relative reduced functional status compared with those undergoing early repair. The echocardiographic and CMR evaluation of RV function are usually related to worse prognosis, recurrency of VT and reduced functional status in patients with repaired TOF. Right ventricular myocardial work index is feasible in patients with repaired TOF; disadvantageous right ventricular work may be a more sensitive indicator of right ventricular impairment compared with standard echocardiographic parameters, and is able to predict exercise capacity.